Postural alterations and their relationship with musculoskeletal pain in nursing staff of a Sicuani Hospital, Cusco 2022: postural alterations and musculoskeletal pain - Fuentes Rivera Mejía, Meyly Reyna (2022)
Abstract Objective: To evaluate the relationship between postural alterations and the level of musculoskeletal pain in the nursing staff of a hospital in Sicuani, Cusco. Materials and methods: Cross-sectional, correlational study carried out in a census sample of 80 nurses. Postural alterations were recorded by means of an evaluation card based on the Standardized Nordic Questionnaire and musculoskeletal pain by means of the VAS scale. Results: 41.3% of the nurses presented severe pain. 45% presented pain in the spine. Forty-five percent present pain in the spine.  There is an association between postural alterations and musculoskeletal pain (x2 = 14.908, sig. = 0.001).  Conclusions: The fact that any prolonged postural alteration in nursing personnel leads to the musculoskeletal pain reported in this study and that, being so, the need to employ strategies that provide a solution for the decrease and improvement of musculoskeletal pain in this occupational group is projected. Key words: musculoskeletal physiological phenomena, musculoskeletal system, musculoskeletal pain, rehabilitation services, posture (Source: MeSH).